The Use of Fable Stories as Learning Media for the Beginner Students of BIPA - Sirmawan Agustinus Balsnimandra Telaumbanua; Jamaluddin Nasution; Romian H Sibarani; Yovita Simangunsong; Sherine Alexandra (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to examine the use of fable stories as a medium for beginner-level BIPA learning through literature studies. BIPA is the abbreviation from Bahasa Indonesia bagi Penutur Asing or like Indonesian for Foreign Speakers. The method used is a descriptive-qualitative review of literature related to fable stories, language learning, and educational technology. The purpose of the study is to examine how fable stories can be used effectively as a medium for beginner-level BIPA learning. The results show that fable stories are effective in improving learners’ language skills and cultural understanding. However, challenges such as adaptation of teaching materials, language complexity, and limited teachers need attention. Digital technology and integration of fables into the curriculum can be innovative solutions. With simple narratives, interesting storylines, and universal moral messages, fables can improve language skills, such as reading, writing, listening, and speaking, while introducing Indonesian cultural values. In conclusion, fable stories have great potential to support BIPA learning, although further development is needed to overcome the existing challenges. Further in-depth research on the effectiveness of fable stories in the context of BIPA needs to be conducted to provide a stronger scientific basis for the development of this teaching method.